2019
DOI: 10.1111/1365-2435.13328
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic and biotic drivers of fatty acid tracers in ecology: A global analysis of chondrichthyan profiles

Abstract: The use of fatty acid (FA) tracers is a growing tool in trophic ecology, yet FA profiles are driven by a number of abiotic and biotic parameters, making interpretation and appropriate use confusing for ecologists. We undertook a global analysis, compiling FA profiles of 106 chondrichthyan (shark, ray and chimaera) populations, as a model to test the utility of FA profiles to partition a priori trophic guilds, phylogeny, water temperature and habitats. Individual FAs characterizing these four factors were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 74 publications
(129 reference statements)
1
47
0
Order By: Relevance
“…Additionally, the lack of change in biomarker profiles attributed to capture, regardless of whether it is due to their overall suitability as stress biomarkers or the proposed limited stress response, encourages the use of amino acids and FAs in white shark ecology. Both amino acids and FAs were influenced by abiotic (temperature) and biotic (size) factors, mirroring their more traditional use in chondrichthyan ecology (Munroe et al 2018, Meyer et al 2019. As such, research teams can confidently apply these biomarkers to questions of white shark diet and habitat use, without the need to incorporate variations in short capture duration, or when precise capture duration may be unknown.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, the lack of change in biomarker profiles attributed to capture, regardless of whether it is due to their overall suitability as stress biomarkers or the proposed limited stress response, encourages the use of amino acids and FAs in white shark ecology. Both amino acids and FAs were influenced by abiotic (temperature) and biotic (size) factors, mirroring their more traditional use in chondrichthyan ecology (Munroe et al 2018, Meyer et al 2019. As such, research teams can confidently apply these biomarkers to questions of white shark diet and habitat use, without the need to incorporate variations in short capture duration, or when precise capture duration may be unknown.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, it appears that amino acids and FAs could serve as informative indicators of the secondary stress response in sharks. While the capture of sharks and rays has been shown to influence blood glucose, lactate, and pH (Moyes et al 2006, Brooks et al 2012, Heard et al 2014, Jerome et al 2018, no studies have examined if capture influences amino acid and FA metabolism in sharks despite the growing popularity of these biomarkers in chondrichthyan ecology (Munroe et al 2018, Meyer et al 2019, leaving a gap in our understanding of how these analytes may be influenced by external stressors.…”
Section: Introductionmentioning
confidence: 99%
“…), as these data were not available for this study. Nonetheless, the data presented here provide the first insight into the trophic dynamics of sharks frequenting the First Coast and present a clear avenue for further work, which may combine data collection on other niche axes with innovative techniques such as compound‐specific SIA (Evershed et al ., ), fatty acid profiles (Meyer et al ., ; Pethybridge et al ., ) and genetic sequencing of faeces, to further explore the extent of trophic synonymy in First Coasts sharks.…”
Section: Discussionmentioning
confidence: 98%
“…In marine environments, many fatty acids have been identified as good tracers of distinct taxa. For example, 16:1n7 and 20:5n3 are indicators of first-order carnivores, 16:0, 18:0 and 22:6n3 of second-order carnivores, and 20:4n6 and 22:4n6 of top predators [38]. 18:0 is also an important tracer of herbivores, and 22:4n6 of planktivores [38].…”
Section: Plos Onementioning
confidence: 99%
“…In relation to fatty acids, marine heterotrophs are subject to biochemical limitations in biosynthesis and modification of carboxylic acids, and generally assimilate dietary fatty acids with little or no modification [37]. Many individual fatty acid tracers (e.g., 20:4n6, 20:5n3, 22:6n3) have been used to study trophic ecology and have revealed the overlapping influences of temperature, habitat, trophic guild and phylogeny (see Meyer et al [38]). Thus, by selecting an appropriate predator, stable isotopes and fatty acids could allow the estimation of trophic structure and its dynamics at multiple time scales.…”
Section: Introductionmentioning
confidence: 99%